2008
DOI: 10.1590/s1516-18462008005000002
|View full text |Cite
|
Sign up to set email alerts
|

Resolução temporal de crianças escolares

Abstract: OBJETIVO: estudar a resolução temporal de crianças com desenvolvimento normal no teste de detecção de intervalos de silêncio (Random gap detection - RGDT) e no teste de detecção do intervalo no ruído (Gaps-in-noise - GIN). MÉTODOS: a população foi composta por 73 crianças escolares, sendo selecionadas 19 com desenvolvimento normal, na faixa etária de seis a 14 anos, de ambos os sexos, ausência de histórico otológico e/ou audiológico e de queixas escolares; audição normal; produção articulatória de todos os son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
12
2
55

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(80 citation statements)
references
References 18 publications
11
12
2
55
Order By: Relevance
“…This data corroborates the findings obtained in other studies that used the RGDT test with pure tone stimuli (10,(12)(13)(14) and they also failed to observe this difference.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This data corroborates the findings obtained in other studies that used the RGDT test with pure tone stimuli (10,(12)(13)(14) and they also failed to observe this difference.…”
Section: Discussionsupporting
confidence: 93%
“…This result agrees with other studies presented in the literature that failed to find differences when the performance of male and female subjects were compared on tests of temporal resolution (7,9,10) . However, these findings disagree with another research (11) in which the mean temporal acuity thresholds of male subjects (7.91 ms) were higher when compared to the mean temporal acuity thresholds of female subjects (11.69 ms), using only the RGDT test version of pure tone stimuli.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results obtained in the Control Group and Study Group approached those found in the literature [10][11][12][13][14][15] . It can be considered that the samples of the present study are within the normal ranges.…”
Section: Discussionsupporting
confidence: 84%